PERFORMANCE OPTIMIZATION TECHNIQUES IN REACT APPLICATIONS: A COMPREHENSIVE ANALYSIS - Veeranjaneyulu Veeri (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Performance optimization remains a critical challenge in modern Reactapplications, particularly as applications scale in complexity and user base. Thiscomprehensive article analysis examines various optimization techniques acrosscomponent-level, application-level, and data handling domains. The article presents asystematic evaluation of key optimization strategies including React.memoimplementation, hook-based optimizations (useCallback, useMemo), code splitting withReact.lazy and Suspense, and efficient large dataset management using ReactVirtualizer. Through detailed case studies of an e-commerce platform and a socialmedia application, we demonstrate significant performance improvements: a 30%reduction in initial load times and enhanced user interaction responsiveness. The article identifies common implementation pitfalls and provides validatedsolutions for issues such as memoization overuse and inefficient component hierarchies.Performance metrics analysis reveals substantial improvements in load time, memoryusage, and overall user experience. The findings provide a structured framework forimplementing optimization strategies while balancing development complexity andmaintenance overhead. This article contributes to the growing body of knowledge onReact application optimization and offers practical guidelines for developers facingsimilar performance challenges.